Las nuevas formas de ciudadanía en las sociedades latinoamericanas contemporáneas - Paola García (Les Cahiers ALHIM)
The subject of citizenship, closely related to the concepts of territoriality and democracy arises and develops in the context of formalization and construction of the liberal State thought from the homogeneous according to the culture and the practices of the dominant groups. The processes of acculturation of the first two-thirds of the twentieth century, are also in the same direction: mix societies. But in the context of globalization, which involves the process of pluralization of societies, the social actors are wondering about the new functions of the State and its citizens. Three social groups, among others, challenge the traditional concept of citizenship: ethnic groups traditionally marginalized and excluded from the political and economic spaces, groups of migrants whose existence takes place in territorialities which are differentiated (country of origin/country of reception) and evangelical groups which claim a citizenship of this world and another in heaven. Our aim in this article is to deal with the current processes which interrogate the citizenship through the plural.